Perception of Medical Professionalism among Clinical Students at Universiti Sains Islam Malaysia (Journal of Medicine, 2017)
Background: Medical professionalism can be defined as a set of values, behaviours and relationships. Thus it is imperative that professionalism is incorporated into the undergraduate curriculum. In Universiti Sains Islam Malaysia, medical professionalism is integrated throughout the 6-year medical programme through courses in Fundamental Islamic knowledge, Medical ethics, clinical teaching and community sessions.Objective: Thus a study was carried out to evaluate the perception of the concept of professionalism among clinical students.Materials and Methods: A cross-sectional study was carried out on 142 clinical students of year 4, year 5 and year 6. Participants were given a questionnaire consisting of items on personality and professional characteristics of a good Muslim doctor. Analysis of data was done using SPSS software version 18. The mean, standard deviation, mean score, median and inter quartile ranges (IR) for knowledge, attitude, practice as well as both personal and professional characteristics were determined and the differences between groups were analysed using Mann-Whitney U tests or T tests.Results: Significant differences were seen for perception of professional characteristics between year 4 and year 6 (p value = 0.0001) and between year 5 and year 6 (p value=0.002). Significant differences for all items on professional characteristics were seen between year 4 and the final year students and four out of five items between year 5 and the final year students. No significant differences were noted in the perception of personal and professional characteristics among the clinical students by gender.Conclusion: The clinical students seemed to have benefitted from the Islamic-integrated medical curriculum in USIM. Overall, the senior clinical students developed better insight of the desirable personal and professional characteristics of a good Muslim doctor. Improvement in the teaching of professionalism could have greater impact on the development of professionalism among the clinical students.J MEDICINE July 2017; 18 (2) : 56-61